Productivity of Zanzibar Tourism Projects Under the Private Direct Investments (1990-99) - Khalfan, Mohammed Hafidh (2002)
Zanzibar islands, in East Africa, form a semi autonomous part of the United Republic of Tanzania. From early 1980's, the Zanzibar Government diversified its economy after realising that its mono-crop economy could not sustain the development momentum, owing to the decline in clove prices, its main cash crop. The isles' diversification measures have resulted in massive inflow of foreign direct investments (FDI). Nominally, it may be remarkable that over 50 percent of the licensed FDI fan in the tourism industry. The industry employs more than 60 percent of the investment workforce. However, in order to achieve Zanzibar's immediate goal of improving development momentum and long-term sustainable growth, it is necessary to empirically understand the performance of this important segment of the diversified economy. The main objective of this study is to explore the general performance of tourism projects under the Zanzibar Private Direct Investments, and the specific objectives are: (i) to provide alternative measures of productivity in the selected establishments; (ii) to compare the productivity pattern between local and foreign owned establishments; and (iii) to measure the contribution of capital and labour inputs to the discovered pattern. Economists claim that, there are two prime sources contributing to economic growth of a nation, employment growth and productivity growth. In exploring the latter, the study uses two models; while the first employs partial indicators, the second on total productivity is based on the framework developed by Gollop and Jorgenson (1979). The results have highlighted the dichotomy of the Zanzibar tourism industry, where large, and well-managed foreign-owned-projects co-exist with smaller, less funded 10caJly owned ones. Using different aggregation methods produced contradicting results. Yet, in overall, the foreign projects outshined the locals in many aspects. For instance, though local projects generated more employment opportunities (59010), indicating their dependence on labour-intensity in production, the foreign projects surpassed their local counterparts in cost competitiveness, efficiency and productivity growth. The results suggest that, more concerted efforts are needed to improve the performance of local investors. The scope of study, however, limits the analysis to the above. In depth analysis of the structure of projects/firms could not be covered due to data constraints.